Dispositions : a debate - Armstrong, D. M. (David Malet), 1926-2014 (International library of philosophy., 1996)
'Why did the window break when it was hit by the stone? Because the window is brittle and the stone is hard; hardness and brittleness are powers, dispositional properties or dispositions.'. Dispositions are essential to our understanding of the world. This book is a record of the debate on the nature of dispositions between three distinguished philosophers - D.M. Armstrong, C.B. Martin and U.T. Place - who have been thinking about dispositions all their working lives. Their distinctive accounts cover many of the issues surrounding dispositions such as the nature of mind, matter, universals, existence, laws of nature and causation. Dispositions illuminates this central topic in analytic philosophy and at the same time highlights deeper concerns of metaphysics.